Organizational commitment, compensation, and competence as drivers of employee performance: Evidence from PT Pegadaian Condet Branch, East Jakarta - Jasodin, Jasodin (Journal of Economics and Business Letters, 2025)
This study examines how organizational commitment, compensation, and competence shape employee performance in a frontline state‐owned financial services context. Using an explanatory, cross-sectional survey of all accessible employees at PT Pegadaian (Condet Branch, East Jakarta; N = 110, April–May 2012), we operationalized commitment (three-component orientation), compensation (perceived fairness, risk-adjusted allowances, benefits), competence (role-relevant knowledge, skills, behaviors), and performance (task and contextual). Assumption checks supported OLS modeling (normal residuals; VIF < 3; Durbin–Watson = 1.721). Bivariate results showed strong, positive associations with performance (commitment r ≈ 0.70; compensation r ≈ 0.64; competence r ≈ 0.81). In the multiple regression, the joint model was highly significant (F = 82.44, p < .001) with substantial explanatory power (R² = 0.700; adj. R² = 0.691). Competence had the largest unique effect (β ≈ 0.640, p < .001), commitment remained a positive predictor (β ≈ 0.257, p = .005), while compensation became non-significant (β ≈ 0.052, p = .564) once the other two were controlled. Findings suggest performance in high-risk branch operations is driven primarily by capability (accurate appraisal, procedural reliability, customer handling) and service-oriented identification with the organization; compensation appears to act indirectly by enabling competence and supporting commitment rather than exerting a large standalone effect. Practical priorities include role-specific competency academies, visible meritocracy to strengthen affective commitment, and risk-aligned but quality-sensitive rewards that reinforce capability and culture.